Sundays with Ron Rozelle - Rozelle, Ron, 1952- (Book collections on Project MUSE., 2009)
When Ron Rozelle and Bill Cornwell, the publisher of The Brazosport Facts, met for their annual lunch, Bill asked what current book Ron was writing. During lunch, they agreed that Ron should try his hand at a weekly column. Ron saw an opportunity both to allow his imagination to wander and to flex his writing muscles. And so, it started. Each week, readers opened their Sunday morning papers to find a column devoted to whatever topic was at hand, be it wizards, geese, holidays, loss, John Wayne, his feline quartet, or sandwiches. Sundays with Ron Rozelle is a collection of these Sunday columns,